2021
DOI: 10.3390/polym14010037
|View full text |Cite
|
Sign up to set email alerts
|

Release of Bisphenol A from Pit and Fissure Sealants According to Different pH Conditions

Abstract: Changes in intraoral pH can cause changes in the chemical decomposition and surface properties of treated resin-based pits and fissure sealants (sealant). The purpose of this study is to evaluate the release of bisphenol A (BPA) from sealants under three different pH conditions over time. The test specimen was applied with 6 sealants 5 mg each on a glass plate (10 × 10 mm) and photopolymerized. The samples were immersed for 10 min, 1 h, and 24 h in solutions of pH 3.0, 6.5, and 10.0 at 37 °C. BPA release was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(43 reference statements)
1
1
0
Order By: Relevance
“…In vitro studies showed BPA and BPA derivatives were detected in saliva. 49,50 These results in line with numerous in vivo studies that tested the BPA and BPA derivatives content in saliva. 48,51,52 Nevertheless, some studies detect the BPA decreased in saliva after placement of dental sealants during several weeks observation period.…”
Section: Bisphenol-a Exposures In Human Salivasupporting
confidence: 79%
“…In vitro studies showed BPA and BPA derivatives were detected in saliva. 49,50 These results in line with numerous in vivo studies that tested the BPA and BPA derivatives content in saliva. 48,51,52 Nevertheless, some studies detect the BPA decreased in saliva after placement of dental sealants during several weeks observation period.…”
Section: Bisphenol-a Exposures In Human Salivasupporting
confidence: 79%
“…It has been confirmed that low pH negatively affects the release of BPA. Therefore, frequent exposure to low pH due to consumption of various beverages after sealant treatment may negatively affect the chemical stability of the sealant in the oral cavity [59]. Composite materials may be considered a potential long-term source of BPA and therefore should not be neglected when assessing overall exposure to endocrine disrupting chemicals.…”
Section: Discussionmentioning
confidence: 99%